Moving Ions Vary Electronic Conductivity in Lead Bromide Perovskite Single Crystals through Dynamic Doping - García‐Batlle, Marisé; Baussens, Oriane; Amari, Smaïl; Zaccaro, Julien; Gros‐Daillon, Eric; Verilhac, Jean‐Marie; Guerrero, Antonio; Garcia‐Belmonte, Germà (Advanced electronic materials, 2020)
Metal halide perovskite single crystals are being explored as functional materials for a variety of optoelectronic applications. Among others, solar cells, field‐effect transistors, and X‐ and γ‐ray detectors have shown improved performance and stability. However, a general uncertainty exists about the relevant mechanisms governing the electronic operation. This is caused by the presence of mobile ions and how these defect species alter the internal electrical field, interact with the contact materials, or modulate electronic properties. Here, a set of high‐quality thick methylammonium lead tribromide single crystals contacted with low‐reactivity chromium electrodes are analyzed by impedance spectroscopy. Through examination of the sample resistance evolution with bias and releasing time, it is revealed that an interplay exists between the perovskite electronic conductivity and the defect distribution within the crystal bulk. Ion diffusion after bias removing changes the local doping density then governing the electronic transport. These findings indicate that the coupling between ionic and electronic properties relies upon a dynamic doping effect caused by moving ions that act as mobile dopants. In addition to electronic features, the analysis extracts values for the ion diffusivity in the range of 10−8 cm2 s−1 in good agreement with other independent measurements. An interplay exists in hybrid perovskites between electronic conductivity and mobile defect distribution within the material. This is observed in high‐quality, thick CH3NH3PbBr3 single crystals. Ionic defect diffusion changes the local doping density then governing the electronic transport. A coupling between ionic and electronic properties relies upon a dynamic doping effect caused by dopant moving ions.